Validity assessment of a third-generation light-induced fluorescence device in detecting proximal and occlusal caries lesions: a cross-sectional study - Bittar, Ahmad; Çetin, Tuba; Başyiğit, Gizem Meva; Gözetici Çil, Burcu (My University, 2024)
Objectives: The objective of this study was to evaluate the efficacy of a quantitative light-induced fluorescence (QLF) device (QrayCam Pro, AIOBIO, Seoul, Republic of Korea) in detecting and differentiating the severity of posterior proximal and occlusal primary caries. Materials and methods: The study included a total of 120 teeth in 60 patients (of both genders, aged between 21 and 38 years) between January and March 2024, one carious tooth and one sound tooth were selected at random in each patient. All occlusal surfaces were evaluated in accordance with the International Caries Detection and Assessment System (ICDAS) Nyvad Criteria, using the visual tactile method. The ICDAS employs a scoring system ranging from 0 to 6, while the Nyvad Criteria employs a similar scoring system. Addionally, the depth of the proximal lesions was scored (0–6) using bite-wing radiography. The quantitative values representing the maximum loss of fluorescence (∆Fmax) and the maximum change in the ratio of red and green fluorescence (∆Rmax) were obtained using the Q-ray Clinical software v 1.45. To assess the validity, the sensitivity, specificity, and area under the receiver operating characteristics curve (AUROC) were calculated. Spearman correlation coefficient was used to investigate the correlation between the findings of the traditional and QLF examination methods. Results: The AUROC values for both ∆Fmax and ∆Rmax were found to be excellent. The sensitivity of QrayCam Pro was found to be 84–88.6%, while the specificity was 100%. The correlation analysis demonstrated a strong correlation between scores obtained from the traditional examination and the QLF values. Conclusions: Based on the findings of this study, QrayCam Pro exhibits potential as a valuable additional tool for not only detecting caries but also for assessing their severity and activity. Clinical relevance: This study revealed that QrayCam Pro might be suggested as a precise tool for enhancing caries detection and assessment compared to traditional methods. By providing quantitative data on caries severity and activity, it enables more informed treatment decisions, potentially optimizing outcomes for patients.
Keywords: Caries Detection; Occlusal Caries; Proximal Caries; Quantitative Light-Induced Fluorescence (QLF)